P031 Post-antifungal effect of the combination of a nidulafungin with amphotericin B and fluconazole against fluconazole-susceptible and resistant Candida albicans. (20th September 2022) - Aslani, Narges
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM:   Objectives: Invasive Candidiasis is a life-threatening condition that kills a large number of immunocompromised patients each year around the world. We used post-antifungal effect studies to analyze the activities of anidulafungin, as a clinically crucial antifungal drug, amphotericin B, and fluconazole (alone and in combinations) against FLC-susceptible and -resistant Candida albicans isolates obtained from the cancer patients. Methods: We tested the phenomenon of post-antifungal effects (PAFEs) of fluconazole (FLC), amphotericin B (AMB), anidulafungin (AFG), and combinations of FLC + AFG, AFG + AMB, and FLC + AMB against 17 C. albicans isolates obtained from the oral cavity of cancer patients. Isolates that had not been exposed to antifungals, served as a control group. Colony counts were performed at 0, 2, 4, 6, and 24 h after a brief (1 h) antifungal exposure. Results: The FLC had no detectable post-antifungal effect independent of antifungal concentration and resembled drug-free FLC (control). When all AMB and AFG were compared with FLC, significant variations in the post-antifungal effect were observed. Combining AFG and AMB with FLC resulted in effective activity compared to FLC alone. Combination regimens were rated as indifferent in general. Interestingly, low dosages of the AFG displayed increasing fungistatic action as it neared a fungistatic endpoint against C. albicans isolates ( n  = 17). Conclusion: Our findings suggest that brief exposure to AFG, in combination with FLC and AMB, at low concentrations of the medicines utilized, could be effective in the evaluation and optimization of new dosage regimens to manage candidiasis. However, future research will look at the clinical utility of our findings.